Facile construction of a polydopamine-based hydrophobic surface for protection of metals against corrosion. Issue 19 (14th February 2017) - Wei, Nan; Jiang, Yueyue; Ying, Ye; Guo, Xiaoyu; Wu, Yiping; Wen, Ying; Yang, Haifeng
Abstract : Metal surfaces with a hydrophobic feature, which could prevent percolation of water droplets and improve their capability against corrosion, arouse extensively interest. Abstract : Metal surfaces with a hydrophobic feature, which could prevent percolation of water droplets and improve their resistance against corrosion, have attracted extensive interest. In this work, we demonstrated a method to prepare a hydrophobic copper surface by coating polydopamine (PDA), and modifying with 1-dodecanethiol (1-DT). Surface hydrophobicity was evaluated by contact angle analysis. Attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), near infrared (NIR) spectroscopy and X-ray photoelectron spectroscopy (XPS) were employed to understand the structure and composition of the resultant coating at the metal surface. The inhibition efficiency of the optimal hydrophobic surface in 3 wt% NaCl aqueous solution, explored by using electrochemical measurements, was 95.3%, which was due to synergy effects of PDA and 1-DT. The promising inhibition of copper corrosion was also validated by scanning electron microscopy observation.